36 Preferred and actual place of death in patients with haematological malignancies. (13th October 2019) - Sheridan, Rebecca; Roman, Eve; Smith, Alexandra; Patmore, Russell; Howard, Martin; Howell, Debra
Abstract : Patients with haematological malignancies are more likely to die in hospital than those with other cancers (Cohen et al. 2015), but little is known about their preferred place of death and the discussions surrounding this. This study aimed to investigate this using data from the Haematological Malignancy Research Network (www.HMRN.org); a population-based cohort that, since 2004, has collected detailed information on all newly diagnosed patients across 14 hospitals (catchment populations ∼4 million). Additional data for the present study were collected from the medical records of 892 HMRN patients (>18 years) who died 2011–2012. Fifty-eight percent of patients died in hospital (home, 20%; care home, 11.9%; hospice, 10.2%). Half had a preferred place discussion recorded, with the majority of these having more than one discussion. At the discussion nearest death, the most common preferred place was home (44.9%)followed by hospice (20%), hospital (19.5%), and care home (15.6%). However, preferences varied over time; for patients whose final recorded preference was hospital, 14.3% had the same preference at their first discussion. When home was the final choice, 80.4% also chose home at their first discussion. Patient involvement was less common during final discussions. Almost all of those who wanted to die in hospital did so, yet only half of those who wanted to die at home achieved this. Although hospital death may sometimes be unavoidable, these findings suggest that greater support may be needed to facilitate discussions and, where possible, enable patients to die in their preferred location.